Improving the Mechanical Strength of Ductile Cast Iron Welded Joints Using Different Heat Treatments - Marques, Eva S.V. (2020)
The main advantage of welding cast iron is to recover parts by repairing defects induced by casting processes (porosities, etc.), before they enter their working cycle, as well as repair cracks or fractures when already in service. This method contributes to decreased foundry industrial waste and avoids the additional energy costs of their immediate recycling. Therefore, it is necessary to have a welded joint with similar or better characteristics than the parent material. The major problem of welding cast iron is that this material has a very high content of carbon in comparison to steel (≈3%). Therefore, when it is heated by the very high temperatures from arc welding and during its process of solidification, very hard and brittle phases originate, known as ledeburite and martensite, and appear in the partially melted zone and in the heat-affected zone. Eventually, this problem can be solved by implementing heat treatments such as preheat or post weld heat treatments under specific parameters. Therefore, in this study, the aim is to collect data about the effects of heat treatments performed at different temperatures on welded joints of high strength ductile cast iron (SiboDur® 450), and to evaluate the effects of heat treatments performed at diverse temperatures on welded joints of this type of material, using Shield Metal Arc Welding and nickel electrodes. Mechanical strength, hardness, and microstructure were analyzed, showing that the best mechanical strength in the joint (380 MPa) was obtained using two passes of E C Ni-Cl (ISO EN 1071:2015) filler metal and post weld heat treatments (PWHT) of 400 °C for two hours.